2020
DOI: 10.1093/omcr/omaa006
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable response of a patient with secondary glioblastoma to a histone deacetylase inhibitor

Abstract: Secondary glioblastoma is a rare brain tumor characterized by a mutation in isocitrate dehydrogenase, which is reported to lead to epigenetic modification. Patients with secondary glioblastoma experience poor survival and quality-of-life outcomes due to the disease’s aggressiveness and a lack of targeted therapies. In this report, a patient with a secondary glioblastoma was treated with a histone deacetylase inhibitor, an epigenetic drug with potent anti-inflammatory properties, in addition to the standard reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Apart from this, epi-drugs can also reduce radiation-induced lung fibrosis ( Wang et al, 2018 ). As such, epi-drugs combined with radiotherapy is gradually showing encouraging results ( Table 2 ; Ree et al, 2010 ; Shi et al, 2016 ; Watanabe et al, 2017 ; Galanis et al, 2018 ; Gurbani et al, 2020 ; Morel et al, 2020 ). As novel medicine and emerging combination therapy are constantly being developed, more clinical trials are needed to verify the efficacy and toxicity of future generations of epi-drugs.…”
Section: Epigenetic Modify Drug Enhances the Function Of Radiotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from this, epi-drugs can also reduce radiation-induced lung fibrosis ( Wang et al, 2018 ). As such, epi-drugs combined with radiotherapy is gradually showing encouraging results ( Table 2 ; Ree et al, 2010 ; Shi et al, 2016 ; Watanabe et al, 2017 ; Galanis et al, 2018 ; Gurbani et al, 2020 ; Morel et al, 2020 ). As novel medicine and emerging combination therapy are constantly being developed, more clinical trials are needed to verify the efficacy and toxicity of future generations of epi-drugs.…”
Section: Epigenetic Modify Drug Enhances the Function Of Radiotherapymentioning
confidence: 97%
“…An ongoing research NCT02137759 aims to assess the use of belinostat in addition to the application of temozolomide and radiotherapy in glioblastoma. A remarkable response of an IDH1mut secondary glioblastoma patient had been reported, who had stable disease for 16 months and consistent improvement in neurocognition over 18 months ( Gurbani et al, 2020 ). In phase I/II trial of vorinostat combined with temozolomide and radiation therapy for newly diagnosed glioblastoma, a shorter PFS and OS was associated with high scores for the vorinostat resistance signature sig-79; conversely, patients with high scores on the vorinostat sensitivity signature, sig-139, had longer PFS (HR, 0.50 [0.29, 0.86], P < 0.05) and OS (HR, 0.45 [0.19, 1.04], P = 0.039) ( Galanis et al, 2018 ).…”
Section: Epigenetic Modify Drug Enhances the Function Of Radiotherapymentioning
confidence: 98%
“…We previously reported interim PFS and sMRI ndings in GBM patients receiving belinostat [12,13]. With 50 months of median follow-up, we report the nal clinical outcomes and tumor recurrence patterns of patients enrolled in this study.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to anti-tumor effects, we reported that belinostat restores the bottle neck enzyme levels of normal brain metabolites, N-acetylaspartate (NAA) and myo-inositol, in vitro to a greater extent than other HDACis [12]. Furthermore, spectroscopic magnetic resonance imaging (sMRI), a quantitative imaging technique that assesses metabolic responses in vivo without any contrast agent injection, has been used to show a GBM patient with an IDH mutation (without MGMT promoter hypermethylation) exhibited remarkable response to belinostat combined with standard chemoradiation therapy [13]. In that case restoration of NAA, creatine and myo-inositol, reached the levels of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anti-tumor effects, we reported that belinostat restores the bottle neck enzyme levels of normal brain metabolites, N-acetylaspartate (NAA) and myo-inositol, in vitro to a greater extent than other HDACis [ 12 ]. Furthermore, spectroscopic magnetic resonance imaging (sMRI), a quantitative imaging technique that assesses metabolic responses in vivo without any contrast agent injection, has been used to show a GBM patient with an IDH mutation (without MGMT promoter hypermethylation) exhibited remarkable response to belinostat combined with chemoradiation therapy [ 13 ]. In that case restoration of NAA, creatine and myo-inositol, reached the levels of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%